High-density lipoproteins as modulators of endothelial cell functions: alterations in patients with coronary artery disease. (15th June 2014) - Kratzer, Adelheid; Giral, Hector; Landmesser, Ulf
Abstract: Alteration of endothelial cell functions, including reduced endothelial nitric oxide (NO) availability, increased endothelial cell apoptosis, adhesion molecule/chemokine expression and pro-thrombotic activation are thought to contribute to the pathophysiology of atherosclerosis and coronary-artery-disease (CAD) with its clinical complications, such as acute coronary syndromes. High-density lipoproteins (HDL) from healthy subjects or reconstituted HDL have been observed to exert potential direct anti-atherogenic effects by modulating these endothelial cell functions. Importantly, endothelial effects of HDL have now been reported to be highly heterogeneous, and are modulated as part of immune responses. More recently, this has also been observed for HDL of patients with CAD, where HDL becomes potentially pro-inflammatory and endothelial-protective properties are markedly altered. Several mechanisms may lead to these altered endothelial effects of HDL in patients with CAD, including oxidative modification of HDL-associated lipids and proteins, such as apoA-I and paraoxonase-1, and alterations of HDL-proteome. These findings have to be considered with respect to interpretation of recent clinical studies failing to demonstrate reduced cardiovascular events by HDL-cholesterol raising strategies in patients with CAD. Both clinical and genetic studies suggest that HDL-cholesterol levels alone are not a sufficient therapeutic target in patients with CAD. The focus of this review is to summarize the role of HDL onto endothelial homeostasis and to describe recently characterized molecular pathways involved. We highlight how structural and functional modifications of HDL particles in patients with CAD may perturb the physiological homeostasis and lead to a loss of endothelial-protective properties of HDL in patients with CAD.